Unisphere under construction
Caption, "New York World's Fair - Washington, still first in war, first in peace and last in the American league, today could boast of a new distinction. It occupies the position of honor on Unisphere. Marked by an American flag (top), the Nation's Capital was part of the final land-mass area affixed to the stainless steel representation of Earth at the Flushing Meadow site of the 1964-1965 New York World's Fair. With Perry Whittaker (bottom center), United States Steel construction super-intendent in charge of the operation, workmen swung the southeastern corner of the United States into place as the permanent symbol of the Fair neared completion above an embryonic reflecting pool. Being built and presented to the Fair by U.S. Steel, the 12-story high Unisphere - largest stainless steel structure in the world - needs only the addition of orbital rings representing satellite flight paths and the installation of lights to mark Washington and 112 other world capitals to be ready well in advance of the fair's opening day, April 22, 1964."